Factors contributing consumer satisfaction with community pharmacies in Kota Kinabalu, Sabah - Lee, Soo Wen (2011)
This study aims to investigate the relationship between dimension of pharmacy services and consumer satisfaction in community pharmacies. A cross-sectional study was conducted among randomly selected consumers who visited six community pharmacies at Kota Kinabalu, Sabah. Self-administered questionnaires were used to collect data. Data analysis included descriptive statistics, factor analysis, reliability test, multiple regression analysis and hierarchical regression analysis. A total of 180 sets of completed questionnaire were used for data analysis. Most of the respondents (48.9%) were at the age range from 21 to 30 years with the mean age of 35 years old. Regression analysis found that there was a significant relationship among dimension of pharmacy services and consumer satisfaction (p{}0.001). Four dimensions of pharmacies like attitude of pharmacy/pharmacist (p{}0.001), availability of OTC drugs and a variety of products (p{}¤0.01), pricing (p[}0.001), and convenient hours (p{}¤0.05) were found to have Significant positive relationship with consumer satisfaction. However, all the moderating variables of age, income status and employment status indicated there were no moderating effects on the relationship among the dimension of pharmacy services and consumer satisfaction (p>.05). This study concluded that there were four key factors contributing consumer satisfaction in community pharmacies at Kota Kinabalu, Sabah. The consumers were most satisfied with the attitude of pharmacy/pharmacist, followed by pricing, availability of OTC drugs and a variety of products and convenient hours. By improving in these key factors, it may provide an opportunity for pharmacist to develop the business strategies for increasing consumer satisfaction.